2019
DOI: 10.21307/jofnem-2019-022
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide adenine dinucleotide induced resistance against root-knot nematode Meloidogyne hapla is based on increased tomato basal defense

Abstract: Root-knot nematodes (RKN; Meloidogyne spp.) are among the most damaging pests to tomato production in the USA and worldwide, with yield losses ranging from 25 to 100%. Host resistance conferred by the Mi gene in tomato is effective against some species of RKN (e.g. M. incognita, M. javanica, and M. arenaria); however, there are virulent species and lines including M. hapla and M. eterolobii that break Mimediated resistance. Plant innate immunity is another possible form of defense against pathogen attack and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The studies reported here demonstrate that, in both growth room and greenhouse experiments, 1mM NAD provided short term protection against M. incognita and enhanced plant growth of tomato. These findings are supported by our previous study where an application of 5 mM NAD resulted in significantly less J2 penetration at 2 DAI, fewer root galls at 30 DAI and better plant growth compared to the non-treated control ( Abdelsamad et al, 2019 ). None of the three NAD concentrations showed any direct nematicidal effect, confirming that the NAD effect is indirect by stimulating plant defenses ( Abdelsamad et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The studies reported here demonstrate that, in both growth room and greenhouse experiments, 1mM NAD provided short term protection against M. incognita and enhanced plant growth of tomato. These findings are supported by our previous study where an application of 5 mM NAD resulted in significantly less J2 penetration at 2 DAI, fewer root galls at 30 DAI and better plant growth compared to the non-treated control ( Abdelsamad et al, 2019 ). None of the three NAD concentrations showed any direct nematicidal effect, confirming that the NAD effect is indirect by stimulating plant defenses ( Abdelsamad et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, we demonstrated that exogenous application of 5mM NAD can induce plant defenses in tomato against the root-knot nematode species, M. hapla and suppress nematode root invasion, root galling and egg production, and at the same time stimulate plant biomass ( Abdelsamad et al, 2019 ). The studies reported here demonstrate that, in both growth room and greenhouse experiments, 1mM NAD provided short term protection against M. incognita and enhanced plant growth of tomato.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies indicate that the role of Rme1 is limited to Mi-1 -mediated resistance only and plays no role in disease resistance [9]. Another compound is nicotinamide adenine dinucleotide (NAD), which induces resistance against RKN pathogenicity, likely through the accumulation of tomato basal defense responses rather than the direct effect on the infective juvenile behavior [67]. In addition, the role of SlWRKY3 acts as a positive regulator for the resistance against the RKN-like M. javanica by activating lipids and the hormone-mediated defense-signaling pathway.…”
Section: The Genetics Of Natural Resistancementioning
confidence: 99%
“…NAD and NAD-cleaving enzymes are also known to impact immunological function in other kingdoms of life. For instance, NAD triggers metabolic profiles in some plants that are associated with resistance to pathogens [ 53 ] and, in tomatoes, NAD has been reported to induce innate immune responses that protect the plants from infection with the root-knot nematode, Meloidogyne hapla [ 54 ]. Additionally, some immune receptors of plants are NADases that have been reported to promote resistance to pathogens [ 55 ].…”
Section: Discussionmentioning
confidence: 99%